الهوية و الغيرية في ساق البامبو لسعود السنعوسي - منصور, آمال (جامعة الوادي - university of Eloued, 2022)
إذا كانت الهوية في مفهومها الأوسع ذلك الإحساس العميق بالانتماء، بالخصوصية، أو ذلك الإدراك الباطني بأنك مختلف عن غيرك، حيث لا يتحقق هذا الإحساس لدى الأنا إلاّ بانتمائك لغويا و دينيا لجماعة بشرية معينة. فعلى الرغم من أن إشكالية الهوية و الغيرية مشكل أنطولوجي أساسا، إلاّ أنها صارت موضوعا خصبا في المشهد الروائي العربي الراهن، ففي "ساق البامبو" لسعود السنعوسي تشكل الهاجس المسيطر في العمل حيث تعالج تركيب الهوية في إئتلافها و اختلافها. يناقش هذا المقال إشكالية الهوية و الغيرية نظريا و تطبيقيا في رواية "ساق البامبو"، و يعتمد على التحليل الثقافي في استقراء تيمات و مضامين العمل If the identity in its largest sense is that deep feeling of affiliation, and of privacy, or that perception that you are different from the other people, where this feeling will not achieved to the ego exept for your affiliation linguistically and religiously to a particular human group. So, in spite of the problematic of the identity and the otherness is basically an ontological problem, but it became a fertile topic in the current arabic narrative scene, in "Bamboo stalk" by Saoud Al Sanaoussi, it makes a dominant obsession in the work where it addresses the structure of identity in its coalition and its differences. This article discusses the problematic of the identity and the otherness theoretically and in practice in the novel of "Bamboo stalk" and it depends on the cultural analysis in the stability of themes and work contents.
مقال
Keywords: الغيرية الأنا الآخرالنسق الثقافي